Fall Armyworm (Spodoptera Frugiperda) in Maize: An Emerging Threat in Nepal and its Management - Kandel, Santosh; Poudel, Rakshya (International Journal of Applied Sciences and Biotechnology, 2020)
Fall armyworm ((Spodoptera frugiperda) commonly known as FAW is polyphagous pest of maize with more than 85 host species. It is native to tropical and subtropical region of America. It has already been detected in India and reports from Nepal also suggests presence of FAW.  Due to Open broader between Nepal and India chance of spreading in Nepal is very high. Delay maturing hybrids and late planted maize crops are likely to be affected by this pest. It can cause serious leaf damage along with direct injury to the ear. Major damage is done by younger larvae. Larvae causes damage by consuming foliage. Terai and inner terai region are considered to be affected more as climatic condition of this region highly favors FAW. So, timely preventive and management practices should be done before it leads to havoc condition. Management of the pest can be done through many biological, chemical and cultural means. Quality seed, Avoidance of late planting, Push-pull technology can be adopted for management practices. Different biological agents have been identified for controlling FAW such as Bacillus thuringenesis (Bt), Baculovirus and Beauveria bassiana etc.  Chemicals like Methomyl, Methyl parathion, chlorpyrifos, malathion, permethrin are used to control the pest. However, use of chemical should be discouraged as it may affect soil fertility and natural enemy of FAW.Int. J. Appl. Sci. Biotechnol. Vol 8(3): 305-309